Related of Whistleblowing System, Academic Funding, and the Implementation of a Green Campus: A Literature Study - Arifah, Siti; Rani, Utpala; Pramudyastuti, Octavia Lhaksmi (Universitas Negeri Semarang, 2023)
This study aims to provide an overview of the development of research related to whistleblowing systems, academic funding, and the implementation of green campuses. This research method uses a literature study, using 811 papers obtained from the scopus.com page and then analyzed using the VOSviewer application. The results of this study show that the number of publications on the topic under study from year to year tends to decrease. Some often-discussed variables include accountability, implementation, compliance, and effectiveness. Authors who publish a lot on this topic are Lewis, D., Vandekerckhove, W., Brown, A.J., and Chang, Y. The conclusion of this study shows that on the topic of the whistleblowing system, academic funding, and the implementation of green campuses, it is still very possible to be developed again because of the need to create a better green campus, so that the implementation of whistleblowing must be maximized and need to pay attention to funding.